From medicinal plant to noxious weed: Bryonia alba L. (Cucurbitaceae) in northern and eastern Europe - Monika Kujawska; Ingvar Svanberg (BMC, 2019)
Abstract Introduction White bryony, Bryonia alba L., is a relatively little known plant in the history of folk medicine and folk botany in eastern and northern Europe. The main aim of this article is to bring together data about Bryonia alba and to summarise its cultural history and folk botanical importance in eastern and northern Europe. Nowadays, this species is considered at best as an ornamental plant, and at worst as a noxious weed. However, ethnographic and historical sources show that it used to be of magical, medicinal and ritual importance in our part of Europe. Methods A diachronic perspective was chosen in order to outline and analyse the devolution and changes in the use of B. alba, in the course of which we take into account the social, ecological and chemical aspects of the usage of this plant. We have therefore traced down and analysed published sources such as ethnographical descriptions, floras, linguistic records and topographical descriptions from northern and central-eastern Europe, particularly Scandinavia, Baltic States, Germany, Poland, Belarus, Ukraine and the Balkan Peninsula. The analysed material is presented and discussed within the biocultural domains that developed in the interaction between human societies and Bryonia alba. Results and discussion Bryonia alba has many folk names in northern and central-eastern parts of Europe: some of them refer to its medicinal properties, life form, odour, or toxicity; others to its possession by the devil. As we learn, Bryonia alba was an inexpensive surrogate for mandrake (Mandragora officinarum L.) and sold as such in the discussed parts of Europe. The folklore and medicinal properties ascribed to mandrake were passed on to white bryony due to an apparent resemblance of the roots. In ethnographic descriptions, we find a mixture of booklore, i.e. written traditions, and oral traditions concerning this species. Some of this folklore must have been an alternative stories spread by swindlers who wished to sell fake mandrake roots to people. Conclusions Plant monographs and reviews of particular species tend to concentrate on the botanicals, which might have great useful potential. White bryony presents a precisely opposite example, being a plant that used to be of medicinal relevance and was furnished with symbolical meaning, and has nowadays preserved only its ornamental value among some urban and rural dwellers of northern Europe. Nonetheless, it might be considered as a part of the biocultural heritage in old, well-preserved gardens. It is still used as a medicine in some parts of the Balkan Peninsula.